Luminescent europium(iii) complexes based on tridentate isoquinoline ligands with extremely high quantum yield. Issue 1 (10th November 2020) - Cai, Zelun; Wei, Chen; Sun, Boxun; Wei, Huibo; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui
Abstract : Synthesis and characterization of two new lanthanide Eu(iii ) complexes based on tridentate isoquinoline ligands with high luminescence efficiency, extended excitation wavelength and good thermal stability. Abstract : Here, we report two europium(iii ) complexes (Eu1 and Eu2 ) with high photoluminescence quantum yield, based on tridentate isoquinoline derivatives (HL1 and HL2 ). The single crystal structures of Eu1 and Eu2 show that three ligands coordinate with an Eu(iii ) ion through diphenylphosphoryl oxygen, pyridyl nitrogen and carboxyl oxygen atoms (O^N^O) with no solvent in the first coordination sphere. An appropriate triplet energy level (about 20 000 cm −1 ) ensures efficient energy transfer from the ligands to the Eu(iii ) ion. As a result, the two complexes exhibited significantly high quantum yields in the solid state (94% and 87% for Eu1 and Eu2, respectively) with excitation bands extending to 350 nm.